Assessment of Environmental Impact by Grocery Shopping Bags An Eco-Functional Approach - Muthu, Subramanian Senthilkannan; Li, Yi.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
This book details the different types of shopping bags used for grocery purposes and their manufacturing processes; various impacts made by different grocery shopping bags in their entire life cycle from cradle to grave stages; importance of consumer behaviour in determining the life cycle impact of shopping bags with the case study of the consumer behaviour studied in different countries for various shopping bags; quantification of environmental impact, ecological sustainability and recyclability potential of various raw materials used for shopping bags; functional and ecological properties of various shopping bags and their assessment; core concept and the theoretical framework of Eco-functional Assessment Methodology; Eco-functional assessment of various grocery shopping bags; quantification of the eco-functional scores of various shopping bags; reduction of environmental impacts of various grocery shopping bags
Basic introduction to shopping bags and eco-functional assessment of shopping bags -- Manufacturing processes of grocery shopping bags -- Life cycle assessment of grocery shopping bags -- Functionality assessment of shopping bags -- Consumption behaviour of shopping bags in various countries: Consumption and eco-impact -- End-of-life assessment of grocery shopping bags -- Eco-functional assessment of grocery shopping bags -- Conclusions.
Keywords: Environmental sciences; Environmental management; Biotechnology; Sustainable development; Environment; Environmental Engineering/Biotechnology.; Production/Logistics/Supply Chain Management; Sustainable Development; Environmental Management